Direct Coombs antiglobulin reactions in Gambian children with Plasmodium falciparum malaria. II. Specificity of erythrocyte-bound IgG. - Facer, C A (1980)
The cause of direct Coombs (DAT) positivity in West African (Gambian) children has been investigated. Results obtained from a comparison of two groups of primary school children, one from an area hyperendemic for P. falciparum malaria and the other partially protected from malaria, indicate an association between a high incidence of DAT positivity and P. falciparum parasitaemia with raised serum antibody titres to falciparum schizonts. Erythrocytes taken from children with a high IgG DAT titre were subjected to acid elution and the eluates examined for IgG content and antigen specificity. Eluted IgG had specific antibody activity against P. falciparum schizont antigen as demonstrated by means of the indirect fluorescent antibody technique. Cross-reaction was not observed with either P. falciparum gametocytes or P. malariae schizonts. No blood group specificity could be demonstrated in either the red cell eluates or serum taken from children with DAT positive red cells. The results provide convincing evidence which implicates falciparum malaria in the aetiology of Coombs positivity in Gambian children. It is probable that erythrocyte sensitization results from passive attachment of circulating complement-fixing malaria antigen-antibody complexes.